The self-reported causes of sleepiness in shift-working tram and truck drivers. (April 2021) - Onninen, Jussi; Pylkkönen, Mia; Hakola, Tarja; Puttonen, Sampsa; Virkkala, Jussi; Tolvanen, Asko; Sallinen, Mikael
Highlights: S hift-working drivers frequently attribute on-duty sleepiness to sleep loss. Tram drivers additionally report insufficient rest breaks as causing sleepiness. Long-haul truckers working night shifts specify time of day as causing sleepiness. Other causes (e.g., traffic, visibility) are not widely linked to severe sleepiness. Future studies should examine task-related sleepiness in occupational driving. Abstract: Identifying the causes of sleepiness in various safety-critical work environments is necessary for implementing more efficient fatigue management strategies. In transportation, little is known about drivers' own perceptions of these causes. Therefore, we instructed shift-working tram (n = 23) and long-haul truck drivers (n = 52) to report at the end of their shifts what made them sleepy if they felt so. These self-reports, measured on-duty sleepiness, and sleep amounts were recorded on every shift over a period of 2–3 weeks per driver. The causes of sleepiness were queried with smartphone applications and sleep logs. Sleepiness was measured with the Karolinska Sleepiness Scale (KSS) and sleep with wrist-worn actigraphs. Data were analyzed using generalized estimating equations. Sleep loss and insufficient rest breaks were commonly reported as causing sleepiness among the tram drivers, whereas time of day and sleep loss were the leading causes among the truck drivers. Other causes, such as traffic or cabin conditions, were not frequently mentioned. During morning, day, and evening shifts, the truck drivers were less likely to report insufficient rest breaks as causing sleepiness than the tram drivers. Similarly, during morning shifts, the truck drivers were less likely to attribute their sleepiness to sleep loss. In shifts with drives reporting severe sleepiness (KSS ≥ 7 at least once, 18–21% of shifts), sleep loss was significantly reported as causing sleepiness among both groups. Reporting insufficient rest breaks was associated with severe sleepiness among the tram drivers, whereas time of day showed the same among the truck drivers. The results highlight the need for addressing sleep-related fatigue in transportation and provide directions for future research with regard to secondary causes of sleepiness.